Distinct Immunogenetic Profiles of Chronic Lymphocytic Leukemia in Asia: A Taiwan Cooperative Oncology Group Registry Study. Issue 12 (25th December 2022) - Yao, Chi-Yuan; Agathangelidis, Andreas; Chuang, Shih-Sung; Tsou, Hsiao-Hui; Feng, Wei-Lien; Liu, Ta-Chih; Chen, Tsai-Yun; Yu, Yuan-Bin; Yeh, Su-Peng; Yao, Ming; Wang, Chuan-Cheng; Lin, Johnson; et al.
Abstract : Asian patientswith chronic lymphocytic leukemia (CLL) exhibit immunoglobulin heavy variable (IGHV) gene repertoires that are distinct from those observed in Western populations, and a higher proportion of Asian CLL patients carry heavy loads of somatic hypermutations (SHM) within the B-cell receptor immunoglobulins (BcR IG). Due to the low regional incidence of CLL in Asia, only a limited number of studies had attempted to probe the phenomenon of BcR IG stereotypy in Asian populations. In this study, we analyzed the IGHV-IGHD-IGHJ gene rearrangements from a series of 255 CLL patients recruited in a nationwide, multicenter study in Taiwan. Our analysis revealed that the IGHV gene repertoire was characterized by evident biases, with IGHV3-7, IGHV4-34, and IGHV3-23 being the most frequent rearranged IGHV genes, and a higher proportion of cases carrying mutated IGHV. In terms of BcR stereotypy, the incidence of major subsets was less frequent in this cohort, with subsets #77 and #28A being the most common, while the incidence of minor subsets was approximately equivalent to that reported in the Western cohorts. With this study, we provide evidence that CLL in Asia is indeed associated with distinct immunogenetic characteristics regarding IGHV gene usage, SHM status, and BcR IG stereotypy.